A Literature Review on Public Leadership in Organizations - Asim Ali; Taha Shabbir; Waqar Ali (Har Press Indonesia, 2022)
The purpose of this study is to analyze the literature on public leadership, to identify emerging methods to research within that discipline, and to recommend potential research directions for the future. Our attention is focused on organisational leadership from the perspective of the PA, as opposed to other types of public leadership, such as political, community, and military leadership, which are discussed elsewhere. While conducting a literature review and analysis of public leadership, this research makes use of a new mix of bibliometric methodologies that have never been used before. The four basic approaches to public leadership (specifically,